(untitled) (World Science, 2018)
At macro and microeconomic levels, household behavior is usually analyzed within the framework of such basic concepts: neoclassicism, institutionalism, and behaviorism. It is noted that a household is a socio-economic object, which has such properties as integrity, hierarchy, integrability, openness, heterogeneity. The research analyzes the peculiarities of the economic behavior of a household as an open socio-economic system, which is formed on the macro level on the principles of organization and self-organization, and at the macro level, quasi-organization, self-organization and self- reflection. In this case, there are natural manifestations of a reflexive approach in cases where relations between elements of the socio-economic system are not relations of direct subordination. The indirect impact on the household’s economic behavior on the part of the state is to translate the motives for decision-making. After all, reflexive management in contrast to the organization does not involve the presence of direct commands, instructions, demonstration of the pattern of behavior, but consists in the transfer of incentives for the desired solutions. At the same time, households can not only perceive differently the controlling influence, but also generate solutions that are not desirable from the standpoint of the state economy, which is multiplied in the conditions of the socio-economic crisis.